Manipulating spin-polarized photocurrents in 2D transition metal dichalcogenides - Xie, Lu; Cui, Xiaodong (Proceedings of the National Academy of Sciences - PNAS, 2016)
Manipulating spin polarization of electrons in nonmagnetic semiconductors by means of electric fields or optical fields is an essential theme of the conceptual nonmagnetic semiconductor-based spintronics. Here we experimentally demonstrate an electric method of detecting spin polarization in monolayer transition metal dichalcogenides (TMDs) generated by circularly polarized optical pumping. The spin-polarized photocurrent is achieved through the valleydependent optical selection rules and the spin–valley locking in monolayer WS₂, and electrically detected by a lateral spin–valve structure with ferromagnetic contacts. The demonstrated long spin–valley lifetime, the unique valley-contrasted physics, and the spin–valley locking make monolayer WS₂ an unprecedented candidate for semiconductor-based spintronics.